A Learning Module for BA Students to Develop ICT Skills for their Learning Activities | Un module de formation visant le développement des compétences TICE chez les étudiants en baccalauréat - Platteaux, Hervé; Hoein, Sergio (Canadian Journal of Learning and Technology, 2015)
This case illustrates the process of developing a learning module to support BA students in their use of ICT (Information and Communication Technology) tools in their learning. At the university where this case occurred, the skill level of ICT use among students in a learning context was very heterogeneous. The E-learning Competency Centre, or ECC, which was in charge of techno-pedagogical development at the institution, created a hybrid learning module that offered students learning materials and activities with both face-to-face workshops and online tutorials for autonomous learning. The students were able to choose subjects they wanted to learn "à la carte" by taking tutorials on their own and/or by participating in face-to-face workshops. The module described in this case is currently under construction. The design phase of this project is the focus of this case study.